Lipocalin-2: a novel link between the injured kidney and the bone. Issue 4 (July 2022) - Courbon, Guillaume; David, Valentin
Abstract : Purpose of review: Fibroblast growth factor 23 (FGF23) excess is associated with left ventricular hypertrophy (LVH) and early mortality in patients with chronic kidney disease (CKD) and in animal models. Elevated Lipocalin-2 (LCN2), produced by the injured kidneys, contributes to CKD progression and might aggravate cardiovascular outcomes. The current review aims to highlight the role of LCN2 in CKD, particularly its interactions with FGF23. Recent findings: Inflammation, disordered iron homeostasis and altered metabolic activity are common complications of CKD, and are associated with elevated levels of kidney-produced LCN2 and bone-secreted FGF23. A recent study shows that elevated LCN2 increases FGF23 production, and contributes to cardiac injury in patients and animals with CKD, whereas LCN2 reduction in mice with CKD reduces FGF23, improves cardiovascular outcomes and prolongs lifespan. Summary: In this manuscript, we discuss the potential pathophysiological functions of LCN2 as a major kidney–bone crosstalk molecule, linking the progressive decline in kidney function to excessive bone FGF23 production. We also review associations of LCN2 with kidney, cardiovascular and bone and mineral alterations. We conclude that the presented data support the design of novel therapeutic approaches to improve outcomes in CKD.